2021
DOI: 10.1002/aws2.1241
|View full text |Cite
|
Sign up to set email alerts
|

Modified clays reduce leaching of per‐ and polyfluoroalkyl substances from AFFF‐contaminated soils

Abstract: Technologies applicable at a field scale to mitigate soil and groundwater pollution by per-and polyfluoroalkyl substances (PFAS) due to the release of aqueous film-forming foams are urgently needed. We demonstrate that modified bentonite clays as soil amendments can effectively reduce the leaching of PFAS from impacted soils. In batch experiments, the significant decrease (95%-99%) of leachable anionic PFAS, including perfluorooctane sulfonate, perfluorohexane sulfonate, and perfluorooctane carboxylate, was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Combustion ion chromatography (CIC) has been a valuable tool to determine total fluorine or total organic fluorine of environmental samples, but such a system is not commonly available. In this topical collection, Wang, Abusallout, et al (2021), Wang, Yan, et al (2021) tested the idea of modifying a total organic carbon analyzer—an instrument common in laboratories across disciplines—as an alternative approach. The modified system can serve as a screening technique or allow for a fluorine mass balance evaluation to help determine overall treatment or percent mineralization for destruction technologies.…”
Section: Sampling and Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combustion ion chromatography (CIC) has been a valuable tool to determine total fluorine or total organic fluorine of environmental samples, but such a system is not commonly available. In this topical collection, Wang, Abusallout, et al (2021), Wang, Yan, et al (2021) tested the idea of modifying a total organic carbon analyzer—an instrument common in laboratories across disciplines—as an alternative approach. The modified system can serve as a screening technique or allow for a fluorine mass balance evaluation to help determine overall treatment or percent mineralization for destruction technologies.…”
Section: Sampling and Analysis Methodsmentioning
confidence: 99%
“…River water and wastewater have similar recoveries to those spiked in deionized water. Wang, Abusallout, et al (2021), Wang, Yan, et al (2021) identified some previously unknown limitations of CIC methods: possible variable recoveries across PFAS of different chain lengths or structures, and inorganic fluorine loss during combustion. The study emphasizes that suitable extraction and inorganic fluoride removal techniques are essential in this analysis to best define whether it is total, organic, or adsorbable organic fluorine.…”
Section: Sampling and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilization/solidification (S/S) technology utilizes conventional soilmixing equipment to distribute stabilizing amendments (with or without solidifying amendments like Portland cement) to immobilize PFAS within the source area. There are multiple bench-scale demonstrations (Barth et al, 2021;Braunig et al, 2021;Hale et al, 2017;Kabiri & McLaughlin, 2021;Kupryianchyk et al, 2016;Sorengard et al, 2019Sorengard et al, , 2021Wang et al, 2021)…”
Section: Stabilization/solidificationmentioning
confidence: 99%
“…A full-scale application of S/S in Canada is currently underway and is using approximately 2% FluoroSorb ® Adsorbent by dry soil weight based on predesign treatability testing. Both bench-scale (Marshall, 2019;Wang et al, 2021;Yan et al, 2020Yan et al, , 2021…”
Section: Fluorosorb For Soil and Groundwatermentioning
confidence: 99%